1996
DOI: 10.1104/pp.112.4.1703
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Oxidative Stress Tolerance in Transgenic Tobacco Plants Overproducing Fe-Superoxide Dismutase in Chloroplasts

Abstract: A chimeric gene consisting of the coding sequence for chloroplastic Fe superoxide dismutase (FeSOD) from Arabidopsis thaliana, coupled to the chloroplast targeting sequence from the pea ribulose-1,5-bisphosphate carboxylase/oxygenase small subunit, was expressed in Nicotiana tabacum cv Petit Havana SR1. Expression of the transgenic FeSOD protected both the plasmalemma and photosystem II against superoxide generated during illumination of leaf discs impregnated with methyl viologen. By contrast, overproduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
131
0
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(139 citation statements)
references
References 44 publications
6
131
0
2
Order By: Relevance
“…Nevertheless, in transgenic tobacco plants, in which an Fe-SOD from Arabidopsis thaliana is overexpressed, induction of cytosolic and chloroplastic CuZn-SODs was suppressed. This suggests that the transgenic Fe-SOD interfered with a pathway signal leading to the induction of CuZn-SODs isozymes, probably because the concentration of O # n − in the chloroplasts is lowered by transgenic Fe-SOD (Van Camp et al, 1996). In our study, the induction of mitochondrial and peroxisomal Mn-SOD and of CuZn-SOD I (Table 3), mainly localized in the cytosol, was brought about by NaCl stress.…”
Section:   mentioning
confidence: 63%
See 1 more Smart Citation
“…Nevertheless, in transgenic tobacco plants, in which an Fe-SOD from Arabidopsis thaliana is overexpressed, induction of cytosolic and chloroplastic CuZn-SODs was suppressed. This suggests that the transgenic Fe-SOD interfered with a pathway signal leading to the induction of CuZn-SODs isozymes, probably because the concentration of O # n − in the chloroplasts is lowered by transgenic Fe-SOD (Van Camp et al, 1996). In our study, the induction of mitochondrial and peroxisomal Mn-SOD and of CuZn-SOD I (Table 3), mainly localized in the cytosol, was brought about by NaCl stress.…”
Section:   mentioning
confidence: 63%
“…These differences in the response to NaCl stress seem to indicate a differential regulation of both SOD isozymes and could also suggest a specific function for each of the enzymes in protecting chloroplasts. The increase in Fe-SOD activity as well as the induction of cytosolic and chloroplastic CuZn-SODs by salt stress have recently been reported in tobacco plants treated with 60 mol m −$ NaCl (Van Camp et al, 1996). Nevertheless, in transgenic tobacco plants, in which an Fe-SOD from Arabidopsis thaliana is overexpressed, induction of cytosolic and chloroplastic CuZn-SODs was suppressed.…”
Section:   mentioning
confidence: 99%
“…Aliquots of frozen fresh shoot material (0.5 g) were ground to a fine powder with liquid nitrogen and homogenized in 1.5 mL of a cold solution containing isoforms were appeared with brown bands after 10 to 20 min at 4°C (Vallejos, 1983). This experiment was repeated three times with similar results.…”
Section: Protein Extractionmentioning
confidence: 84%
“…Several genes encoding for plant antioxidant enzymes have been cloned, characterized, and used in the construction of transgenic lines. Transgenic plants overexpressing SOD (Bowler et al, 1991;Van Camp et al, 1996;Breusegem et al, 1999;Alscher et al, 2002;Feki et al, 2016), APX (Wang et al, 1999), GR (Foyer et al, 1995), GPX (Roxas et al, 1997(Roxas et al, , 2000 and CAT (Feki et al, 2015) showed tolerance to various abiotic stresses.…”
Section: Introductionmentioning
confidence: 99%
“…An NaCl-tolerant cultivar of pea, compared with a sensitive cultivar, had enhanced chloroplastic and cytosolic CuZn-SOD activity when treated with NaCl (Hernandez et al, 1995). In transgenic tobacco plants, salt stress was associated with overexpression of cytosolic and chloroplastic CuZn-SOD enzymes (Van Camp et al, 1996). Drought stress represents another oxidative environmental factor causing enhanced production of O # d − and H # O # , particularly in chloroplasts (Price & Hendry, 1989Smirnoff, 1993 ;Bohnert et al, 1995).…”
Section:       mentioning
confidence: 99%